PEMBERDAYAAN MASYARAKAT MELALUI DIVERSIFIKASI PRODUK PANGAN LOKAL BERBASIS BIJI JAWAK (SETARIA ITALICA) UNTUK PENCEGAHAN STUNTING DAN UPAYA PENGUATAN EKONOMI MASYARAKAT DESA JERORA SATU KABUPATEN SINTANG - Sunarti; Uray B. Asnol; Ria Damayanti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2025)
Sintang Regency is classified as a disadvantaged area with an extreme poverty status in Indonesia, and is one of the priority regions targeted in the National Action Plan for the Acceleration of Development in Disadvantaged Areas. Jerora Satu Village is one of the 29 villages in Sintang District, Sintang Regency, West Kalimantan. Sintang Regency is one of the regencies that directly borders a neighboring country, namely Malaysia, specifically the Sarawak region. The natural resource potential of Jerora Satu Village includes plantations and horticultural agriculture. One of the leading commodities originating from Jerora Satu Village is jawak (Setaria italica) and sweet corn. Jawak has strong potential as an alternative food crop, considering its nutritional content and its ability to grow in dry–climate areas. The nutritional content of jawak is three to five times higher than that of rice and wheat. The majority of residents rely on the agricultural, plantation, or fisheries sectors for their livelihoods. However, household income remains low due to limited technological support for diversified economic development and restricted access to wider markets. In addition, health problems such as stunting among toddlers have been identified; out of 108 toddlers, 20 (20.37%) were found to be stunted. Based on these issues, the proposed community empowerment program by BEM is titled: "Community Empowerment Through Diversification of Local Food Products Based on Jawak (Setaria italica) Seeds for Stunting Prevention and Strengthening the Economy of Jerora Satu Village, Sintang Regency." The Community Empowerment activities through the Diversification of Local Food Products Based on Jawak (Setaria italica) Seeds have been successfully carried out in Jerora Satu Village, Sintang Regency, by the BEM BERDAMPAK STIKARA team with support from the Directorate of Community Service (DPPM), Directorate General of Higher Education, Science and Technology. The program aims to increase the utilization of local food for stunting prevention while strengthening the household economy in Jerora Satu Village by involving local MSME partners and the Jerora Satu Village PKK group. To support the production process, the implementing team provided six production tools, including a rotary–type grain dryer machine as production support equipment. This machine functions to speed up the drying process of jawak seeds without reducing their nutritional quality, while increasing time and labor efficiency. Equipment provided to MSME partners included a grinder machine, an automatic band sealer, and a vacuum fryer. For the PKK partners, the team provided a grain dryer, a dough–mixing machine for bread, and a noodle–making machine. Abstrak Kabupaten Sintang termasuk dalam kategori daerah tertinggal dengan status kemiskinan ekstrim di Indonesia, dan termasuk salah satu daerah prioritas untuk target capaian Rencana Aksi Nasional Percepatan Pembangunan Daerah Tertinggal di Indonesia. Desa Jerora Satu merupakan salah satu dari 29 desa yang ada di Kecamatan Sintang, Kabupaten Sintang, Kalimantan Barat. Kabupaten Sintang merupakan salah satu kabupaten yang berbatasan langsung dengan negara tetangga yaitu Malaysia, khususnya wilayah Sarawak. Potensi sumber daya alam di Desa Jerora Satu diantaranya adalah perkebunan dan pertanian holtikultura. Salah satu komoditas unggulan yang berasal dari Desa Jerora Satu adalah Jawak (Setaria Italica) dan jagung manis. Tanaman jawak memiliki potensi yang sangat baik sebagai tanaman pangan alternatif ditinjau dari aspek kandungan gizi, dan kemampuan tumbuhnya di daerah beriklim kering. Kandungan gizi dari jawak tiga sampai lima kali lebih baik dari beras dan gandum. Mayoritas penduduk menggantungkan hidup pada sektor pertanian serta perkebunan atau perikanan. Namun, pendapatan warga tetap rendah karena minimnya dukungan teknologi untuk pengembangan ekonomi yang lebih beragam dan terbatasnya akses ke pasar yang lebih luas. Selain itu, ditemukan masalah kesehatan yaitu stunting pada balita, dari 108 balita diketahui 20 balita (20,37%) yang mengalami stunting. Berdasarkan permasalahan tersebut maka program pemberdayaan masyarakat oleh BEM yang diusulkan adalah "Pemberdayaan Masyarakat Melalui Diversifikasi Produk Pangan Lokal Berbasis Biji Jawak (Setaria Italica) Untuk Pencegahan Stunting Dan Upaya Penguatan Ekonomi Masyarakat Desa Jerora Satu Kabupaten Sintang". Kegiatan Pemberdayaan Masyarakat melalui Diversifikasi Produk Pangan Lokal Berbasis Biji Jawak (Setaria italica) telah berhasil dilaksanakan di Desa Jerora Satu, Kabupaten Sintang oleh tim BEM BERDAMPAK STIKARA dengan dukungan dari DPPM Direktorat Jendral Pendidikan Tinggi bidang Saintek. Program ini bertujuan untuk meningkatkan pemanfaatan pangan lokal dalam pencegahan stunting sekaligus memperkuat ekonomi keluarga Desa Jerora Satu dengan melibatkan mitra UMKM dan PKK Desa Jerora Satu. Untuk mendukung proses produksi, tim pelaksana menyerahkan 6 alat produksi yaitu mesin pengering biji-bijian tipe rotary dryer yang diberikan sebagai alat bantu produksi. Mesin ini berfungsi untuk mempercepat proses pengeringan biji jawak tanpa mengurangi kualitas gizi, sekaligus meningkatkan efisiensi waktu dan tenaga, alat pada mitra UMKM menyerahkan mesin Grinder, bansealer otomatis dan Vacuum Frying, pada Mitra PKK menyerahkan Pengering Biji bijian, Mesin Mixing adonan roti, Mesin cetak mie.